Language matters: Analysing the national environmental policy of India (2006) from an ecolinguistic discourse analytic perspective - Mohan, Midhun (International Journal of Publication and Social Studies, 2024)
This study aims to scrutinize the discursive practices which are as important as the practical steps when it comes to environmental management. The role of discursive practices when it comes to environmental preservation is overlooked by the practitioners. While the previous studies were focusing more on the political and ideological side of the policy taken for the study, the discursive side remained unexamined. By focusing more on the harmful discursive practices regrading environment such as anthropocentric language, phrases, usages used in the National environment policy, the study offers a fresh perspective to Indian environmentalism and policymaking regarding environment. By analyzing the environment policy under the lens of Ecolinguistic discourse analysis, the invisible disparities that are there in the policy will be made perceptible. The study also highlights the importance of incorporating Indian ecosophy (ecological philosophy) when formulating such policies, which advocates interconnectedness, interdependence and environmental stewardship. By addressing and rectifying harmful discursive usages, policymakers can contribute to enhancing environmental awareness, correcting misconceptions and fostering a deeper understanding of the interconnected relationship between humans and environment. The findings of the study remind of the need for holistic and inclusive linguistic usages and the problematic side of the existing language used in the environmental policy.